Socio-Spatial Determinants of Accessibility and Utilization of Pediatric Services in Kinshasa, Democratic Republic of the Congo - Bukaya, Jean Pierre Kambondji; Mululu, Patrick Ngoie; Kamanda wa Kamanda, Jean Claude; Kabata, Kabamba; Loukia, Aketi (European Journal of Science, Innovation and Technology, 2026)
This study examines the socio-spatial determinants of accessibility to and utilization of pediatric services in Kinshasa. Using survey data from 1,164 parents and guardians and a series of binary logistic regression models, the analysis explores how geographic position, household socio-demographic profile, transport conditions, perceived barriers, and prior care experiences shape the choice between formal pediatric consultation and self-medication or other non-medicalized practices. The results show pronounced territorial inequalities in the distribution of respondents and in the spatial pattern of pediatric consultation and self-medication across the city. Among the respondents, 67.27% reported resorting to pediatric consultation while 32.71% relied on self-medication or related informal practices. In the bivariate models, consultation was significantly associated with male parenthood, health insurance for the child, non-biological caregiving, higher income brackets, and the use of motorized or public transport. By contrast, walking, lack of transport, and lack of information reduced the odds of formal consultation. In adjusted models, older parental age remained negatively associated with consultation, whereas male sex, Protestant affiliation, higher monthly income, older child age, public transport use, and some disease contexts increased the likelihood of consultation. Perceptions of service quality showed mixed and sometimes paradoxical effects: courtesy encouraged consultation, but long waiting times consistently reduced it, while evaluations of care quality were not uniformly associated with formal care-seeking. Overall, access to pediatric services in Kinshasa is jointly structured by socio-economic resources, mobility conditions, perceived constraints, and uneven urban geography. Policies that improve transport access, reduce waiting time, strengthen financial protection, and correct spatial disparities in service distribution could increase timely pediatric care utilization.